Tempo de transformação: a religiosidade em trajetórias de jovens universitários sem religião - Ribeiro, Iago Rodrigues (2018)
This work verses about the construction of subjectivity of young people that define themselves as “without religion” in Fortaleza. It is an effort to note the several meanings that the religious can cover in contemporary society, including manners of believe and non-believe, seeking to explore important aspects of the interlocutor´s trajectory. The text is supported by interviews conducted among young people, men and women from Fortaleza that study in the Center of Humanities of the Federal University of Ceará and that comprehend themselves as without religious bond. This work questions plural forms of religious identity construction, considering youth as a category socially constructed and as generational moment marked by the possibility of elaborating a number of behaviors that can be relevant in the formation of the individual subjectivity. The analysis shows how an contrastive identity to religious can ground itself in other values, such as experimentation, autonomy, sexual liberty, equality. I discuss about themes like religion and it´s control device nature, religious pluralism and secularism, coming from oral reports of participants of a sociability network situated in the Center of Humanities of the Federal University of Ceará – located in the Benfica district, in the city of Fortaleza. Coming from this reflection, I seek to instigate questionings about the religious dimension in the contemporary society, with the intention of comprehend how it´s presence is relevant in the social dynamic and in the public space.